Pengaruh Dana Desa Terhadap Kesejahteraan Masyarakat di Desa Sidomulyo Kecamatan Biru-Biru Kabupaten Deli Serdang - Irianto Nasution; Badaruddin Badaruddin; Lindawati Lindawati (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
The purpose of this study was to analyze community perceptions, the influence and strategies of managing village funds on the welfare of the community in Sidomulyo Village, Biru-Biru District, Deli Serdang Regency. The analytical method used in this study is a quantitative method using primary data and secondary data. The indicators in this study are village funds, transparent, accountable, participatory, community welfare, social justice, economic justice, and democratic justice. This study uses a simple linear regression analysis and SWOT. The results showed that the calculation obtained that the value of village funds had a positive effect on community welfare, with a coefficient value of 1.036. In other words, increasing village funds will improve the welfare of the community. Given the value of Sig. = 0.000 0.05, it is concluded that village funds have a significant effect on community welfare. The right strategies used in managing village funds for community welfare are (1) utilizing information systems to improve the village economy; (2) developing the potential of young human resources in the position of village development strategy; (3) utilize village assistants in planning the development of village infrastructure facilities/infrastructure; and (4) channeling village funds appropriately in order to increase the productivity of rural communities.